Cardiac evaluation of patients with 22q11.2 duplication syndrome. Issue 3 (27th December 2020) - Butensky, Adam; de Rinaldis, Chiara Pandolfi; Patel, Shrey; Edman, Sharon; Bailey, Alice; McGinn, Daniel E.; Zackai, Elaine; Crowley, T. Blaine; McDonald‐McGinn, Donna M.; Min, Jungwon; Goldmuntz, Elizabeth
Abstract: The 22q11.2 duplication syndrome (22q11.2DupS) is characterized by phenotypic heterogeneity, from seemingly asymptomatic to severely affected patients. Our study sought to detail the cardiac phenotype associated with 22q11.2DupS, the prevalence of aortic arch anomalies and aortic root dilation in 22q11.2DupS, and to assess how frequently new congenital heart disease (CHD) is diagnosed at outpatient cardiac evaluation following genetic diagnosis. In our cohort of 85 patients, 20.0% had CHD, with a wide range of phenotypes. Sixty‐eight patients had complete cardiac evaluations detailing aortic arch sidedness and branching pattern, of which 5 (7.4%) had an aortic arch anomaly, all of whom had concurrent intracardiac CHD. Of 53 patients without CHD who had complete cardiac evaluations, only 3 (5.7%) had evidence of aortic root dilation. Of 46 patients who underwent outpatient cardiac evaluation following diagnosis of 22q11.2DupS, only one (2.2%) was found to have CHD, an isolated bicuspid aortic valve without stenosis. Therefore, the CHD phenotype in 22q11.2DupS, when present, is heterogeneous. Aortic arch anomalies are uncommon, and no patient in our cohort had one in isolation. Isolated aortic root dilation is also uncommon. Finally, outpatient cardiac evaluation following genetic diagnosis without previously known CHD infrequently identified minor cardiac malformations.